Testing of the mechatronic robotic system of the differential lock control on a truck. (27th October 2017) - Kučera, Pavel; Píštěk, Václav
This article deals with testing the algorithm developed for autonomous control lock of the differential in a truck. Hardware for hardware in the loop testing of robotic systems or automotive systems is used and the proposed control algorithm was implemented into it. The system was applied to a vehicle with 8 × 8 drive and control algorithm evaluates input sensor values to set robotic console control. It is an actuator which consists of electrovalve, pneumatic cylinder, console, special dog clutch and feedback limit switch. This robotic console is used to lock the truck differentials. Verification of the correct algorithm operation was performed by manoeuvres and the response of the whole system was monitored. The aim was to get the reaction times of this mechatronic robotic system and evaluate them.